Heterotopic Triplet Pregnancy after In Vitro Fertilization with Favorable Outcome of the Intrauterine Twin Pregnancy Subsequent to Surgical Treatment of the Tubal Pregnancy. (12th January 2014) - Felekis, Theodoros; Akrivis, Christodoulos; Tsirkas, Panagiotis; Korkontzelos, Ioannis
Abstract : Heterotopic triplet pregnancy is an exceptionally rare medical condition. The broad use of assisted reproductive technologies has contributed to the increase of ectopic and subsequently heterotopic pregnancy rate, masking a life-threatening condition for the gravid and the intrauterine pregnancy. We describe a case of a woman with heterotopic triplets at 9 +4 gestational week following transfer of three embryos obtained by in vitro fertilization techniques. The ectopic tubal pregnancy was ruptured and salpingectomy was performed by laparotomy. The intrauterine pregnancy progressed to the delivery by cesarean section of two healthy twins at 36 +2 gestational age. Heterotopic triplets with tubal ectopic are a special diagnostic and therapeutic challenge for the obstetrician. High index of suspicion and timely treatment by laparotomy or laparoscopy can preserve the intrauterine gestation with a successful outcome of the pregnancy.